Formation des collections archéologiques et ethnographiques : notes sur des trajectoires d’objets latino-américains - Vanessa Bernal Multon (Les Cahiers de l'École du Louvre)
The archaeological and ethnographic objects from Latin America now in museums have had several “lives”. “Lives” that began when they were made and that continued thanks to their discovery. Studying their histories, the different itineraries they have followed until they arrived in Europe and in particular their entries into French museums, is an important step in the analysis of the building up of collections in France. This article presents the itineraries of five archaeological objects, from Peru and Mexico, which are now in the public collections of French museums.